Lessons Learned in Pilot Testing Specialty Consultations to Benefit Individuals with Lower Limb Loss - Christine Elnitsky; Gail Latlief; Deborah Gavin-Dreschnack; Melanie Harris; Robert Campbell (International Journal of Telerehabilitation)
Telerehabilitation technologies enable the delivery of rehabilitation services from providers to people with disabilities as well as specialty care consultations. This article discusses the barriers experienced when planning and pilot testing a telerehabilitation multi-site specialty consultation for specialists in their medical centers, and the lessons learned. The barriers included integration and participation, coordination across organizational units, and privacy and information security. Lessons learned included the need for collaboration across multiple departments, telerehabilitation equipment back-ups, and anonymous and private communication protocols. Despite delays resulting from coordination at multiple levels of a national organization, we developed a program plan and successfully implemented a pilot test of the southeast region program.  Specialty consultation using telerehabilitation delivery methods requires identifying provider preferences for technological features. Lessons learned could inform development of outpatient telerehabilitation for patients with amputations and studies of patients and providers involved in telerehabilitation.